Peculiarities of future law enforcement officers' psychological readiness for professional stress in war conditions - Цільмак, Олена Миколаївна; Цільмак, О. М.; Tsilmak, Olena M.; Shvets, Dmytro V.; Швець, Дмитро Володимирович; Швець, Д. В.; Kisil, Zoriana R.; Кісіль, Зоряна Романівна; Кісіль, З. Р.; Pasko, Olha M.; Пасько, Ольга Миколаївна; Пасько, О. М.; et al. (Warsaw : «Aluna Publishing», 2025)
Materials and Methods: During 2023-2025, the research was conducted among cadets of the 3rd training years (2023-2024, Group A, n = 114) and (2024- 2025, Group B, n = 112) aged 18-22 years who undertook their utilization tours in practical police units (for 3 months): Group A without prior professional and psychological training, Group B – after preliminary correctional and psychological work. Results: It has been established that the specifics of the professional activities of law enforcement officers under martial law have a negative impact on the indicators of their psycho-emotional state and stress resilience. At the same time, targeted correctional and psychological work with cadets reduces the magnitude of negative changes in all diagnostic indicators: in Group A, the indicators of well-being, activity and mood significantly (p . 0.05-0.01) deteriorated by 0.6, 0.7 and 1.2 points, and in Group B – by 0.4, 0.4 and 0.5 points, respectively (p > 0.05); the indicators of psychological stress, stress resilience, predisposition to develop stress, endurance under stress in Group A deteriorated significantly (p . 0.05-0.01) by 6.2, 3.9, 4.9, 5.1 points, and in Group B – unreliably (p > 0.05) by 4.3, 2.6, 3.4 and 2.9 points, respectively. Conclusions: It has been proven that a well-organized professional and psychological training contributes to improving the level of future law enforcement officers’ psychological readiness for professional activities under the influence of wartime stress factors.
Shvets D. V. Peculiarities of future law enforcement officers' psychological readiness for professional stress in war conditions / D. V. Shvets, Z. R. Kisil, O. M. Pasko et al. // Wiadomosci lekarskie (Warsaw, Poland : 1960). – Warsaw : «Aluna Publishing», 2025. – 78(8). - P. 1488- 1495. URL: https://doi.org/10.36740/WLek/209501
Keywords: psychological readiness; professional stress; future law enforcement officers; professional activities; war